Mental health outcomes before psychotropic medications: a retrospective case series of one state hospital records from 1945 to 1954 - Ann Chapleau; Jennifer Harrison; Stephen Love; David Sherman (BMC, 2023)
Abstract Background Current outcomes for mental illness are widely regarded as poor. Since the introduction of psychotropic medications in the mid 1950's, previous psychosocial practices were minimized in favor of medication focused treatment. The majority of large U.S. state hospitals have closed with records destroyed or in storage, inaccessible to researchers. This creates barriers to studying and comparing outcomes before and after this shift in treatment practices. Aims The study aim was to examine discharge outcomes in relation to length of stay and diagnosis in one U.S. state hospital. Methods This case series study examined 5618 medical records of participants admitted to one state hospital from 1945 to 1954, the decade prior to adoption of psychotropic medications. Results Of the 3332 individuals who left the facility, over half (59.87%) of first episode hospitalizations were discharged within 1 year, and 16.95% were hospitalized for more than 5 years. 46.17% of all admissions were discharged from hospital with no readmission. The most common diagnoses included schizophrenia, other forms of psychosis, and alcoholism. In the decade before the introduction of psychotropic medications, participants were often admitted for a single episode and returned to their homes within several years. Conclusions Although limited to one site, findings suggest that discharge outcomes prior to psychotropic medication as a primary treatment for mental illness may be more positive than previously understood.